A New Classification of Spreader Flap Techniques - Wurm, Jochen; Kovacevic, Milos (Facial Plastic Surgery, 2013)
The objective of this study was to introduce various spreader flap technique modifications to adjust the width of the middle nasal vault in patients who underwent rhinoplasties with humpectomy. Decisive modifications of current spreader flap techniques were performed to allow a more natural restoration of the middle nasal vault and the internal nasal valve after humpectomy. Additional steps provide tools to adjust the width and shape of the middle nasal vault according to patients' requirements. The techniques were categorized into “basic spreader flaps,” “flaring spreader flaps,” “support spreader flaps,” and “interrupted spreader flaps.” The various spreader flap techniques were used during 576 primary septorhinoplasties in patients with hump noses, hump/crooked noses, or hump/tension noses. The average follow-up was 19 months. Patients who received basic spreader flaps or a flaring spreader flaps tended to show a slightly too wide middle nasal vault, revision surgery was necessary in four of these cases. All other patients showed an appropriate width in the middle nasal vault and an aesthetically pleasing course of the dorsal aesthetic lines. No signs of inverted v deformities or collapse of the internal nasal valve were observed in any of the patients. Patients who had reported impaired nasal breathing preoperatively described clearly improved subjective symptoms. The described techniques appear to be appropriate and highly promising as a supplement to existing procedures for reconstructing the middle nasal vault and internal nasal valves. No additional cartilage grafts are needed.
Keywords: spreader flaps; internal nasal valve; middle vault; inverted v deformity